The Role of Music Art in the Cultural and Spiritual Life of Uzbekistan - Ph.D. Zakirova Zilola Azamovna (Zien Journals, 2023)
Culture is a tool that speaks about the past, present and future of a nation and introduces it to the world. This article talks about the attention paid to the field of culture and art in the modernizing Uzbekistan, the measures that are being implemented and planned to be implemented in the future
Keywords: New Uzbekistan; action strategy; development strategy